2022
DOI: 10.1177/00220345221092752
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Atlas of Gingival Mucosa in Type 2 Diabetes

Abstract: The oral gingival barrier is a constantly stimulated and dynamic environment where homeostasis is often disrupted, resulting in inflammatory periodontal diseases. Type 2 diabetes (T2D) has been reported to be associated with gingival barrier dysfunction, but the effect and underlying mechanism are inconclusive. Herein, we performed single-cell RNA sequencing (scRNA-seq) of gingiva from leptin receptor-deficient mice ( db/db) to examine the gingival heterogeneity in the context of T2D. Periodontal health of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In our analysis, T cells consisted of 2.5% of the total immune cells isolated from the periodontium. Others have similarly analyzed Cd45+ immune cells isolated from the periodontium of mice via scRNAseq and showed a T cell fraction that was comparable 32 or markedly greater 33 to our T cell fraction. Identifying multiple T cell clusters in our data set may have been achieved by performing a second re-clustering analysis using a higher resolution of only T cells.…”
Section: Discussionmentioning
confidence: 52%
“…In our analysis, T cells consisted of 2.5% of the total immune cells isolated from the periodontium. Others have similarly analyzed Cd45+ immune cells isolated from the periodontium of mice via scRNAseq and showed a T cell fraction that was comparable 32 or markedly greater 33 to our T cell fraction. Identifying multiple T cell clusters in our data set may have been achieved by performing a second re-clustering analysis using a higher resolution of only T cells.…”
Section: Discussionmentioning
confidence: 52%
“…However, whether MGFs also possess SCC-like potential and participate in the regulation of periodontal homeostasis via taste transduction pathway has yet to be investigated. We first re-analyzed sequence data deposited in the GEO RNA-seq database ( 24 , 25 ). We found that the expression of Tas2r143 was only reported in 2 of the 6 RNA-seq databases, and only one of these databases reported the expression of Gnat3.…”
Section: Discussionmentioning
confidence: 99%
“…The gingival ILCs expressed Rorc , Il17a, and Il17f, but not Tbx21 and Gata3, indicating that they were ILC3s. Notably, recent clinical studies have reported the presence of ILCs in gingiva from human periodontitis patients ( Brown et al, 2018 ; Dutzan et al, 2016 ) and leptin receptor-deficient mice ( Wang et al, 2022 ), although their pathological contributions have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%